Early life seizures and epileptic spasms in -related disorders - Thalwitzer, Kim M.; Xian, Julie; de Campo, Danielle; Parthasarathy, Shridhar; Magielski, Jan; Sullivan, Katie R.; Goss, James; Rigby, Charlene Son; Boland, Michael; Prosser, Ben; Ruggiero, Sarah M.; Syrbe, Steffen; et al. (Epilepsia, 2024)
Objective Individuals with disease-causing variants in STXBP1 frequently have epilepsy onset in the first year of life with a variety of seizure types, including epileptic spasms. However, the impact of early onset seizures and antiseizure medication (ASM) on the risk of developing epileptic spasms and impact on their trajectory are poorly understood, limiting informed and anticipatory treatment, as well as trial design. Methods We retrospectively reconstructed seizure and medication histories in weekly intervals for individuals with STXBP1 developmental and epileptic encephalopathy (DEE) with epilepsy onset in the first year of life and quantitatively analyzed longitudinal seizure histories and medication response. Results We included 61 individuals with early onset seizures, 29 of whom had epileptic spasms. Individuals with neonatal seizures were likely to have continued seizures after the neonatal period (25/26). The risk of developing epileptic spasms was not increased in individuals with neonatal seizures or early infantile seizures (21/41 vs. 8/16, odds ratio [OR] = 1, 95% confidence interval [CI] = .3-3.9, p = 1). We did not find any ASM associated with the development of epileptic spasms following prior seizures. Individuals with prior seizures (n = 16/21, 76%) had a higher risk of developing refractory epileptic spasms (n = 5/8, 63%, OR = 1.9, 95% CI = .2-14.6, p = .6). Individuals with refractory epileptic spasms had a later onset of epileptic spasms (n = 20, median = 20 weeks) compared to individuals with nonrefractory epileptic spasms (n = 8, median = 13 weeks, p = .08). Significance We provide a comprehensive assessment of early onset seizures in STXBP1-DEE and show that the risk of epileptic spasms is not increased following a prior history of early life seizures, nor by certain ASMs. Our study provides baseline information for targeted treatment and prognostication in early life seizures in STXBP1-DEE.
Gesehen am 18.11.2024